Antigen detection of rabies virus in brain smear using direct Rapid Immunohistochemistry Test - R, Damayanti; I, Rahmadani; Y, Fitria (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Rabies is zoonotic disease caused by a fatal, neurotropic virus. Rabies virus is classified into the Genus of Lyssavirus under the yang family of Rhabdoviridae. Rabies affecting hot- blooded animals, as well as human. Dogs, cats, monkeys are the vectors or reservoirs for rabies and the virus was transmitted through the saliva after infected animalâs bites. The aim of this study was to conduct rapid diagnosis to detect rabies viral antigen in brain smear using immunohistochemical (IHC) method namely direct Rapid Immunohistochemical Test (dRIT). A total number of 119 brain samples were achieved from Bukittinggi Veterinary Laboratory, West Sumatra. Standardisation and validation of the method were compared to Fluorescent Antibody Test (FAT) as a golden standard for rabies diagnosis. Results show that dRIT was a very good method, it can be performed within two hours without the need of fluorescent microscope. The samples were tested using FAT and from 119 samples tested, 80 (67.23%) samples were positive for rabies and 39 (32.77%) samples were negative for rabies whereas using dRIT showed that 78 (65.54%) samples were positive for rabies and 41 (34.45%) samples were negative for rabies. The dRIT results were validated by comparing them with FAT results as a golden standard for rabies. The relative sensitivity of dRIT to FAT was 97.5% and the relative specificity to FAT was 100% (with Kappa value of 0.976, stated as excellent). The achievement showed that dRIT is very potential diagnostic tool and is highly recommended to be used widely as a rapid diagnosis tool for rabies. Key Words: Rabies, Antigen Detection, Immunohistochemistry, Direct Rapid Immunohistochemical Test (dRIT)